The Relationship between Husband and Wife's Understanding of Pre-Marriage Course Material and Family Behavior in Batipuh District, Tanah Datar Regency - Wahyuni Sekar Dini; Ismaniar Ismaniar (Universitas Negeri Padang, 2023)
This research was motivated by the poor behavior of husband and wife in the family, which resulted in an increase in the divorce rate in Batipuh District, Tanah Datar Regency from 2020 - 2021, which was 291 cases. The increase in the divorce rate was caused by the husband and wife having attended a premarital course program. This is presumably due to the low understanding of the husband and wife on the premarital course material. This study aims to see a picture of a married couple's understanding of the premarital course material, to see the behavior of a married couple in a family, and to see the relationship between the two. This type of research is correlational with a quantitative approach. The population in this study were 250 married couples who had received a Prenuptial Course at the KUA, Batipuah District. The sample is taken as much as 20% of the sample is as many as 50 husband and wife couples. The sampling technique uses a convenient type of probability sampling. The collection technique uses a questionnaire, while the data collection tool is a list of statements. The data analysis technique of this research uses percentage and product moment. The results of this study can be seen that: (1) The understanding of married couples about premarital course material in Batipuh sub-district, Tanah Datar Regency is quite adequate, (2) The behavior of husband and wife in family life in Batipuh District, Tanah Datar Regency is classified as poor. , (3) There is a significant relationship between the understanding of married couples on premarital course material with their behavior in the family. Suggestions from this study are addressed to premarital course participants in order to improve the application of premarital course materials in families, to premarital course managers to add and develop materials that are really needed by married couples in building a harmonious family, and to further researchers in order to deepen this study with different variables.